Alternative Pathways to Ciprofloxacin Resistance in Neisseria gonorrhoeae: An In Vitro Study of the WHO-P and WHO-F Reference Strains - Natalia González; Saïd Abdellati; Irith De Baetselier; Jolein Gyonne Elise Laumen; Christophe Van Dijck; Tessa de Block; Chris Kenyon; Sheeba Santhini Manoharan-Basil (MDPI AG, 2022)
Emerging resistance to ceftriaxone and azithromycin has led to renewed interest in using ciprofloxacin to treat Neisseria gonorrhoeae. This could lead to the rapid emergence and spread of ciprofloxacin resistance. Previous studies investigating the emergence of fluoroquinolone resistance have been limited to a single strain of N. gonorrhoeae. It is unknown if different genetic backgrounds affect the evolution of fluoroquinolone resistance in N. gonorrhoeae, as has been shown in other bacterial species. This study evaluated the molecular pathways leading to ciprofloxacin resistance in two reference strains of N.gonorrhoeae-WHO-F and WHO-P. Three clones of each of the two strains of N.gonorrhoeae were evolved in the presence of ciprofloxacin, and isolates from different time points were whole-genome sequenced. We found evidence of strain-specific differences in the emergence of ciprofloxacin resistance. Two out of three clones from WHO-P followed the canonical pathway to resistance proceeding via substitutions in GyrA-S91F, GyrA-D95N and ParC. None of the three WHO-F clones followed this pathway. In addition, mutations in gyrB, uvrA and rne frequently occurred in WHO-F clones, whereas mutations in yhgF, porB and potA occurred in WHO-P.